Circulating miR-326 could serve as a predictive biomarker for response to neoadjuvant chemotherapy in locally advanced cervical cancer - Zou, Kangni; Yang, E.; Cui, Tao; Li, Zhengyu (Frontiers in Oncology, 2022)
Background: Clinically, couples of patients with locally advanced cervical cancer (LACC) are insensitive to neoadjuvant chemotherapy (NACT). Recent studies have reported that circulating microRNAs (miRNAs) may be involved in the response to NACT. The aim of this study was to discover the potential miRNAs which can predict the response to NACT in LACC. Methods: Pair-matched blood samples of 39 LACC patients before and after receiving NACT were collected. Seven paired samples were used for microRNAs microarray analysis. Targeted miRNAs were selected by bioinformatics analysis and were validated by quantitative reverse transcription-polymerase chain reaction (qRT-PCR). All 39 patients were assigned into responders group and non-responders group after NACT. The predictive performance of selected microRNA was evaluated by the sensitivity, specificity, accuracy and the area under the receiver operating characteristic (ROC). Results: A total of 17 miRNAs down-regulated before NACT and up-regulated after NACT were selected out according to microarray analysis in our previous study, and miR-326 and miR-376a-3p were selected for further exploration. According to the responses and the evaluation criteria, there are 25 patients reached partial response (PR) and 14 patients remained stable. Further qRT-PCR analysis showed that miR-326 significantly down-regulated before NACT and up-regulated after NACT in 12 responders (p=0.02). The expression of miR-376a-3p showed no statistical difference before and after NACT in these 12 responders. Then, miR-326 provided an AUC-ROC of 0.75 (p=0.04) in the discrimination between responders and non-responders group. The cut-off value of ROC for miR-326 to predict the response of NACT was＜0.023, the sensitivity was 88.89% and the specificity was 50%. Conclusions: The expression of miR-326 significantly up-regulated after NACT in responders. miR-326 may be a biomarker for predicting the response to NACT in LACC patients. The results maybe optimize individualized treatments for LACC patients.